The Relationship Between the Incidence of Malnutrition Status with Exclusive Breastfeeding for Toddlers 0-59 Months at Posyandu Kenanga Subang Regency - Karim, Fatmawati; Mustika, Mela (Universitas Ibn Khaldun Bogor, 2024)
Nutrition is a public health problem associated with mortality and morbidity in toddlers. One of the things that is thought to be related to the incidence of malnutrition in toddlers is exclusive breastfeeding. This study aims to analyze the relationship between the incidence of undernutrition with exclusive breastfeeding in toddlers. Method: The type of Research is an analytical survey with a crossectional approach. The total sampling was 47 people. The Independent variable is the incidence of malnutrition while the dependent variable is exclusive breastfeeding. Results: as many as 58% of toddlers were malnourished, and as many as 57.4% did not get exclusive breastfeeding. The results of statistical tests using chi-square with a significance value of P = 0.000 smaller than the set p of <0.05 then the hypothesis is accepted. Conclusions and suggestions: there is a relationship between the incidence of malnutrition in toddlers and exclusive breastfeeding. Further research is needed related to factors related to malnutrition with other variables as controllers.